2010
DOI: 10.1109/tnsre.2010.2047656
|View full text |Cite
|
Sign up to set email alerts
|

Psychophysiological Responses to Robotic Rehabilitation Tasks in Stroke

Abstract: This paper presents the analysis of four psychophysiological responses in post-stroke upper extremity rehabilitation. The goal was to determine which psychophysiological responses would provide the most reliable information about subjects' psychological states during rehabilitation. Heart rate, skin conductance, respiration, and skin temperature were recorded in a stroke group and a control group during two difficulty levels of a pick-and-place task performed in a virtual environment using a haptic robot and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
36
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(44 citation statements)
references
References 34 publications
4
36
0
2
Order By: Relevance
“…that were induced by a psychological stimulus (mental and cognitive tasks, physical tasks, psychological tasks, etc.). The relationship between psychophysiological parameters and complexity of the tasks is not always unique and is actually very complex [1][2][3][4], because the physiological response is also subject to large interpersonal differences [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…that were induced by a psychological stimulus (mental and cognitive tasks, physical tasks, psychological tasks, etc.). The relationship between psychophysiological parameters and complexity of the tasks is not always unique and is actually very complex [1][2][3][4], because the physiological response is also subject to large interpersonal differences [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…However, in the field of ASP, we assume the latter instead of the former. Recent application areas include Brain Computer Interfaces (BCI) [486,637,683], medical applications (e.g., sedation of patients [249] and rehabilitation [489]), and, as already mentioned, affective loops [83,288,654].…”
Section: The Closed Loop Modelmentioning
confidence: 99%
“…For example, it has been shown that emotions influence our cardiovascular system [276,400,493,495,496,589,659] and, consequently, can shorten or prolong life [204,205,298,299,423,598]. Moreover, emotions also play an important role with chronic diseases [42,46], cancer (e.g., coping strategies) [343,645], and rehabilitation [489], to mention three. [174, p. vii].…”
Section: Health Informaticsmentioning
confidence: 99%
“…Tiberio et al (2012) use psychophysiological measures to study the response to a telepresence robot of elderly people suffering from mild cognitive impairment-a mobile robot mounted with a screen allowing a human to interact with the user via videoconference. Psychophysiological measures have also been used in the context of virtual rehabilitation where stroke patients used a haptic robotic interface that allowed them to feel virtual objects (Goljar et al 2011;Novak et al 2010). For completeness, we also mention other studies we are aware of where psychophysiology has been used in human-robot interaction, even though these studies have very different objectives from our own.…”
Section: Related Literaturementioning
confidence: 99%